An Incidental Finding of Spontaneous Hepatic Artery Thrombosis in a Healthy Patient - Joelle St-Pierre; Deepa Suryanarayan; Ah-Ling Cheng; Stephen E. Congly (Annals of Internal Medicine: Clinical Cases)
Hepatic artery thrombosis (HAT) outside the setting of liver transplantation is exceedingly rare. Few cases of HAT leading to hepatic infarction have been reported, and management strategies have varied from symptom control to anticoagulation and antiplatelet therapy. Cases of spontaneous HAT without hepatic dysfunction, however, have not been previously reported. We report the case of an incidentally found spontaneous HAT without signs of hepatic dysfunction or injury in an otherwise healthy 45-year-old woman. Treatment consisted of therapeutic anticoagulation and antiplatelet therapy. Resolution of the HAT was confirmed by follow-up ultrasound imaging, and the patient remained free of HAT at 12-month follow-up magnetic resonance imaging.